Perancangan Karya Busana Evening dari Bahan Batik Nitik dengan Sumber Ide Bunga Kemuning - Ms Jumariah; Sri Purwani; Maya Rustiandari (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2020)
Evening dress is clothing made from a nice material and an interesting decoration that looks beautiful and the dress in the age of the long dress is worn at the party night. Evening dress accentuates the majesty of Fashion aesthetics, both in terms of model and colour harmony. This is what motivates the writer to make creativity making